Induced Pluripotent Stem Cells with a Mitochondrial DNA Deletion123. (5th July 2013) - Cherry, Anne B. C.; Gagne, Katelyn E.; Mcloughlin, Erin M.; Baccei, Anna; Gorman, Bryan; Hartung, Odelya; Miller, Justine D.; Zhang, Jin; Zon, Rebecca L.; Ince, Tan A.; Neufeld, Ellis J.; Lerou, Paul H.; et al.
Abstract In congenital mitochondrial DNA (mtDNA) disorders, a mixture of normal and mutated mtDNA (termed heteroplasmy) exists at varying levels in different tissues, which determines the severity and phenotypic expression of disease. Pearson marrow pancreas syndrome (PS) is a congenital bone marrow failure disorder caused by heteroplasmic deletions in mtDNA. The cause of the hematopoietic failure in PS is unknown, and adequate cellular and animal models are lacking. Induced pluripotent stem (iPS) cells are particularly amenable for studying mtDNA disorders, as cytoplasmic genetic material is retained during direct reprogramming. Here, we derive and characterize iPS cells from a patient with PS. Taking advantage of the tendency for heteroplasmy to change with cell passage, we isolated isogenic PS‐iPS cells without detectable levels of deleted mtDNA. We found that PS‐iPS cells carrying a high burden of deleted mtDNA displayed differences in growth, mitochondrial function, and hematopoietic phenotype when differentiated in vitro, compared to isogenic iPS cells without deleted mtDNA. Our results demonstrate that reprogramming somatic cells from patients with mtDNA disorders can yield pluripotent stem cells with varying burdens of heteroplasmy that might be useful in the study and treatment of mitochondrial diseases. STEM CELLS2013;31:1287–1297